How is personality related to intelligence and achievement? A replication and extension of Borghans et al. and Salkever. (1st June 2017) - Lechner, Clemens; Danner, Daniel; Rammstedt, Beatrice
Abstract: In two equally enlightening contributions on identification problems in personality psychology, Borghans, Golsteyn, Heckman, and Humphries (2011) and Salkever (2015) discussed two questions with potentially far-reaching implications for studies on the effects of cognitive ability on important life outcomes: (1) whether measures of "achievement" and "intelligence" are distinct; (2) and to what extent achievement measures are confounded with personality traits. In the present article, we revisit this controversy, identify unresolved issues, and provide a fresh look at the key questions. Our independent replication and extension using a large representative sample of German ninth-grade students ( N  = 13.648) demonstrates that achievement and intelligence tests are highly but not perfectly correlated. Personality accounts for a substantial share of the variance in achievement but only a small share of that in intelligence. Importantly, personality incrementally explains variance in achievement above and beyond intelligence. Whereas standardized achievement measures are a good (but not "pure") indicator of cognitive ability, this problem of confounding is particularly pressing for school grades, which are only modestly correlated with intelligence and highly laden with personality. We discuss theoretical implications and recommend that studies aiming to identify the effects of cognitive ability on life outcomes routinely control for personality. Highlights: We revisit the relationships between personality, intelligence, and achievement. Achievement tests and intelligence (reasoning) correlate highly but not perfectly. School grades (9th grade) correlate only moderately with intelligence. Achievement measures are substantially confounded with personality traits. Studies on the effects of cognitive ability should control for personality traits.